2005
DOI: 10.1080/10715760500306695
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic characterization of oxidative dysfunction in human umbilical vein endothelial cells (HUVEC) induced by exposure to oxidized LDL

Abstract: The oxidative modification of low-density lipoprotein (LDL) and subsequent alteration of endothelial cell function are generally accepted as an important early event in the pathogenesis of atherosclerosis. To understand the mechanism by which oxidized LDL (oxLDL) causes dysfunction in endothelial cells, human umbilical vein endothelial cells (HUVEC) were exposed to oxLDL at a concentration that induces cellular dysfunction, and proteomic analysis was carried out, together with the analysis of cellular lipid pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Studies also link NPM to the onset of atherosclerosis. Human vascular endothelial cells treated with oxidized low density lipoprotein show dephosphorylated levels of NPM correlating with decreased proliferation and increased cellular dysfunction [66], consistent with studies demonstrating enhanced endothelial cell proliferation correlating to increased NPM phosphorylation upon treatment with cardioprotective drugs [67]. …”
Section: Nucleolar Proteins Associated With Cardiac Pathophysiologysupporting
confidence: 62%
“…Studies also link NPM to the onset of atherosclerosis. Human vascular endothelial cells treated with oxidized low density lipoprotein show dephosphorylated levels of NPM correlating with decreased proliferation and increased cellular dysfunction [66], consistent with studies demonstrating enhanced endothelial cell proliferation correlating to increased NPM phosphorylation upon treatment with cardioprotective drugs [67]. …”
Section: Nucleolar Proteins Associated With Cardiac Pathophysiologysupporting
confidence: 62%
“…On the other hand, phosphorylation on one or more of its four serine residues reduces its MT‐destabilizing activity. Alteration in stathmin expression has been reported in human malignancies (Belletti et al, 2008) and in HUVEC cells under oxidative stress condition (Kinumi et al, 2005). Our data reported show, for the first time, that also weightlessness heavily affects the expression levels of this protein (Figures 2 and 3A).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the mechanism by which oxLDL causes dysfunction in EC, HUVEC were exposed to oxLDL at a concentration that induces cellular dysfunction. Results showed that nucleophosmin, stathmin, and nucleolin were differentially expressed after exposure to oxLDL [68]. Caveolae and rafts are specialized microdomains of the EC plasma membrane, which play an important role in signal transduction, transcellular transport, and cholesterol homeostasis.…”
Section: Ecmentioning
confidence: 99%